Mixed-effects random forest for clustered data - Hajjem, Ahlem; Bellavance, François; Larocque, Denis (Journal of statistical computation and simulation, 2014)
This paper presents an extension of the random forest (RF) method to the case of clustered data. The proposed 'mixed-effects random forest' (MERF) is implemented using a standard RF algorithm within the framework of the expectation-maximization algorithm. Simulation results show that the proposed MERF method provides substantial improvements over standard RF when the random effects are non-negligible. The use of the method is illustrated to predict the first-week box office revenues of movies.